Directors’ Personal Liability in Corporate Bankruptcy: An Analytical Study on the Application of the Business Judgment Rule and the Doctrine of Gross Negligence - Donny Ferdiansyah; Mulyati, Agustine Susi; Majuri; Toyib Zainal; Edi Mulyadi (International Journal of Education, Vocational and Social Science, 2026)
This study aims to examine in depth the concept of directors’ personal liability in the bankruptcy of Limited Liability Companies (PT), focusing on the application of the Business Judgment Rule principle and the doctrine of gross negligence within the framework of Indonesian corporate law. The issue of directors’ liability in bankruptcy situations is crucial, as the boundary between managerial error and acceptable business risk is often difficult to define. This research employs a normative juridical method using statutory, conceptual, and case approaches by analyzing relevant legislation, commercial court decisions, and corporate law literature. The results of this study indicate that the Business Judgment Rule serves as a legal safeguard for directors who act in good faith, with due care, and in the best interests of the company. However, this principle cannot be used as a defense when gross negligence is proven — that is, the failure of directors to perform their managerial duties reasonably, resulting in losses or the company’s bankruptcy. In such circumstances, directors may be held personally liable under Article 97 paragraphs (3) and (5) of Law Number 40 of 2007 concerning Limited Liability Companies. Therefore, this study emphasizes the importance of prudence, professional conduct, and accountability among directors in business decision-making to prevent abuse of authority and minimize the risk of personal liability in bankruptcy situations.